Records ruin the landscape : John Cage, the sixties, and sound recording - Grubbs, David, 1967- (Duke University Press, 2014)
John Cage's disdain for records was legendary. It was shared by other experimental and avant-garde musicians in the 1960s. Scholar and longtime musician David Grubbs explores the present-day musical landscape, as listeners encounter experimental music through the recorded artifacts of composers and musicians who largely disavowed recordings.